Epidemiological profile of American tegumentary leishmaniasis in the municipality of Manhuaçu, state of Minas Gerais, Brazil (Veterinária Notícias, 2020)
American Tegumentary Leishmaniasis (ATL) is a widely distributed anthropozoonosis caused by theprotozoa Leishmania spp. and is considered a serious public health problem. We aimed to assessManhuaçu’s burden caused by ATL through the profiling of all ATL case reports during the period from2010 to 2015. A descriptive, ecological and retrospective study of the confirmed cases of ATL wascarried out using data regarding the age, sex, area of residence, type of entry (new case or recurrence),and clinical form of the disease of the existing registered reports provided by the Sistema de Informaçãode Agravos de Notificação (SINAN). We observed that the first quarter of the years showed highernumber of reports. The 58 notifications were classified as a first time occurrence, being 95% of thecutaneous form of the disease, and 76% of the cases in male patients. Regarding the location of theinfection, 86% of the patients belonged to the rural area, and most (60%) were between 20 and 59 yearsold. Thus, the epidemiological profile of infections of ATL in Manhuaçu, MG indicates that maleindividuals aged between 20 and 59 years old and living in rural areas are more likely to get infected.Moreover, it is important to know the epidemiological profile of ATL cases for adequate healthsurveillance and prevention of the disease on this region.